39: TREATMENT OF ANASTOMOTIC LEAKAGE AFTER ESOPHAGECTOMY (TENTACLE—ESOPHAGUS) STUDY: EFFICACY OF DIFFERENT INITIAL TREATMENT STRATEGIES FOR ANASTOMOTIC LEAKAGE. (23rd April 2022) - Ubels, S; Verstegen, M; Bouwense, S; Hannink, G; Siersema, P; Klarenbeek, B; Van Workum, F; Rosman, C
Abstract: Background and aim: Anastomotic leakage (AL) is a common and severe complication after esophagectomy. It is largely unknown which primary treatments are most effective for which type of leak. We aimed to investigate the effectiveness of different primary treatments of AL after esophagectomy. Methods: The TENTACLE—Esophagus study is an international retrospective cohort study, in which 1509 patients with AL after esophagectomy between 2011 and 2019 were included. Detailed data were collected regarding case mix, resection (e.g. minimally invasive resection), leakage characteristics (e.g. organ failure, leak circumference, intrathoracic contamination) and leakage treatment (e.g. hours from diagnosis to treatment, primary and secondary treatment modalities such as endoscopic, radiologic and surgical treatment). An elaborate data quality validation and data accuracy assessment were performed. Primary outcome was 90-day mortality and secondary outcomes included length of stay and leak healing time. Regression analysis will be used to analyze the effectiveness of primary treatments after correction for patient-, surgery-, and leakage characteristics, and leakage severity. Different clinically relevant leakage groups have been defined. Efficacy of different treatment strategies adjusted for leakage severity will be analyzed in these clinical groups. The full study protocol is accessible at www.tentaclestudy.com . Results: Detailed data of 1509 patients with AL was collected from 71 centers in 20 countries. Data accuracy was 96.5%. Preliminary results showed that the overall 90-day mortality was 11.7%. The analysis of TENTACLE—Esophagus data is currently being performed and efficacy of different leakage treatment strategies is being assessed. The efficacy of initial leakage treatment strategies will be ready to be presented at the ESDE meeting. Conclusion: This is the largest study on effectiveness of AL treatments. The final results on efficacy of primary leak treatments, which will be available for presentation at the ESDE meeting, could provide an evidence-based basis that can be used by clinicians to determine the preferred primary treatment strategy in patients with a given type of anastomotic leakage after esophagectomy.